Analog multiplexer for testing multianode photomultipliers used in AMIGA project of the Pierre Auger Observatory - Lucero, Agustín (2015)
Most particle detectors used in astroparticle physics have an optoelectronic device that senses generated light and converts it into an electrical pulse. Photomultiplier tubes are commonly used, particularly those with multiple anodes. Prior to coupling to a detector system these tubes must be fully characterized, which requires either the same number of data acquisition channels as outputs or a switching-multiplexer system. Given that every project has its own requirements, the testing system must be as flexible as possible. The multiplexer presented here can be used to test silicon photomultipliers or any high-frequency signal. It is a scalable 64 to 4 channel analog devicedesigned for low crosstalk and low attenuation. Results of the application of this multiplexer with a −3 dB bandwidth of 800 MHz are shown by testing 64-channel tubes for the AMIGA project.